The changing influence of city-systems on global shipping networks: An empirical analysis - César Ducruet; Sylvain Cuyala; Ali EL Hosni (Journal of Shipping and Trade (JST), 2016)
This paper revisits the classical issue of port-city relationships by applying for the first time network analytical methods to maritime flows connecting cities of the world, over the period 1950-1990. A global matrix of interurban vessel flows was elaborated for about 600 cities using data from the Geopolis and Lloyd's Shipping Index databases and the rigorous assignment of ports to both coastal and inland urban areas. Main results show that although the largest cities have witnessed a diminishing importance in world traffic, they have maintained their dominance in the network in terms of centrality and geographic reach. This research thus contributes to question the ineluctable separation between ports and cities which dominated the literature, while offering new empirical evidence about the structure and dynamics of city-systems and spatial networks in general.
Keywords: 650; City-system; Graph theory; Maritime network; Urban development; World shipping